Catalytic supercritical water gasification mechanism of coal. (20th March 2020) - Ge, Zhiwei; Guo, Liejin; Jin, Hui
Abstract: Catalytic supercritical water gasification (SCWG) for H2 production is a hopeful way of coal conversion to replace the traditional coal utilization mode. At present, the detailed catalytic mechanism in the process remains unknown. Herein, a comprehensive catalytic SCWG mechanism of coal is proposed by establishing a novel catalytic kinetic model. It shows that catalysts (K2 CO3 ) break up the coal matrix by a cyclic redox reaction to produce plenty of mesopores, accelerating steam reforming of fixed carbon and coal pyrolysis. Water-gas shift reaction is facilitated by K2 CO3 via formation of formate, which then promotes steam reforming of CH4 at high temperature (≥700 °C) due to the decreasing CO. The proposed mechanism provides important insights in catalytic SCWG process of coal. Graphical abstract: Image 1 Highlights: A catalytic supercritical water gasification mechanism of coal is proposed. A kinetic model for catalytic supercritical water gasification of coal is developed. K2 CO3 facilitates not only steam reforming of fixed carbon, but also coal pyrolysis. Steam reforming of CH4 at high temperature (≥700 °C) is promoted by K2 CO3 .